Comprehensive geophysical, geotechnical, and geochemical assessments of an offshore landfill in Singapore - Zhang, Zhibo (2024)
Comprehensive site investigation techniques, including Electrical Resistivity Tomography (ERT), Induced Polarization (IP), Multichannel Analysis of Surface Waves (MASW), and Microtremor Array Method (MAM), were integrated with geotechnical and geochemical tests of retrieved waste samples from Singapore's operational offshore landfill. The properties of landfill wastes vary widely, including shear-wave velocities 127-248 m/s, densities 1.2-2.1 Mg/m3, resistivity 3.0-25.3 Ω∙m, and chargeability 48-82 mV/V. The natural clay layer underneath was clearly delineated and effectively mitigated leachate leakage. K-means clustering of the geophysical data facilitates precise mapping of waste distribution and quantities of recoverable metals based on quantitative criteria. This study illustrates a thorough case study adopting the new site investigation and characterization paradigm for an offshore landfill, which provides insights into leachate leakage detection and evaluations of landfill mining and resource recovery.